Walking the Line: Balancing Access to Research and Protecting Prisoners. (21st January 2019) - Van Westendorp, Mathijs; Lierman, Steven
Abstract: Prisoners are often excluded from participating in clinical research (ie clinical trials and clinical investigations related to medicinal products and medical devices) due to the historical precedent of their abuse and exploitation. The exclusion of prisoners from clinical research is often deemed necessary to guarantee their protection from such abuse and exploitation. However, in this article, we argue that the right to science, which encompasses the right to access the benefits of science and research participation, is an emerging human right that is applicable to prisoners and may only be limited when this is necessary and proportionate. Whether this is necessary depends in part on the validity of a prisoner's informed consent. We discuss the importance of prison conditions for voluntary consent and examine the relationship between prison overcrowding and sub-par prison conditions by analysing the jurisprudence of the European Court of Human Rights on Article 3 of the European Convention on Human Rights on the prohibition of torture and inhuman treatment. We contend that the special circumstances of being in prison warrant additional protective measures, concurring with the Belgian Advisory Committee on Bioethics that research without the explicit aim of improving the situation of the individual prisoner or the prison community should be excluded. Given the complexity of the question of whether prisoners can give valid informed consent, rigorous oversight by an ethics committee with expertise concerning the prison system is necessary to provide a proportional balance between offering prisoners access to research and protection from abuse and exploitation.